2022
DOI: 10.14814/phy2.15480
|View full text |Cite
|
Sign up to set email alerts
|

Role of macrophages during skeletal muscle regeneration and hypertrophy—Implications for immunomodulatory strategies

Abstract: Skeletal muscle is a plastic tissue that regenerates ad integrum after injury and adapts to raise mechanical loading/contractile activity by increasing its mass and/or myofiber size, a phenomenon commonly refers to as skeletal muscle hypertrophy. Both muscle regeneration and hypertrophy rely on the interactions between muscle stem cells and their neighborhood, which include inflammatory cells, and particularly macrophages. This review first summarizes the role of macrophages in muscle regeneration in various a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 196 publications
0
10
0
Order By: Relevance
“…After an injury, neutrophils are the first immune cells to invade the injury site where they attract monocytes and start the inflammatory response. 32,33 This could therefore explain the larger infiltration of macrophages after severe than mild damage, even though additional studies are needed to describe the kinetics of neutrophil infiltration after electrically-evoked LC. We also showed that the number of macrophages was not different between the two damaging protocols during the proliferating phase of MuSCs (i.e., from day 1 to day 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After an injury, neutrophils are the first immune cells to invade the injury site where they attract monocytes and start the inflammatory response. 32,33 This could therefore explain the larger infiltration of macrophages after severe than mild damage, even though additional studies are needed to describe the kinetics of neutrophil infiltration after electrically-evoked LC. We also showed that the number of macrophages was not different between the two damaging protocols during the proliferating phase of MuSCs (i.e., from day 1 to day 3).…”
Section: Discussionmentioning
confidence: 99%
“…34 Although several pro-myogenic/trophic secreted factors from antiinflammatory/restorative macrophages (e.g., IGF-1, TGFβ, GDF3, etc.) 32 have been described during the regenerative inflammation phase of muscle repair after toxic injury, further investigations are needed to determine the influence of muscle damage severity on the inflammatory profile of macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular environment of contractile fibers is highly complex and contains myogenic stem cells (MuSCs), mesenchymal stromal cells (MSCs), such as fibro/adipogenic progenitors (FAPs), and resident macrophages [ 204 , 205 , 206 ]. Muscle-specific satellite cells are positioned between the sarcolemma membrane and basal lamina.…”
Section: Skeletal Muscle Heterogeneity and Muscle Proteomicsmentioning
confidence: 99%
“…Though, accessing this process is difficult due to the multiple cells, mediators and pathways involved. This process and its resolution are driven by a complex set of mediators that regulates cellular events required to clear inflammatory cells from sites of infection and injury and the restoration of tissue function [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%